SPIRITUAL PRAGMATICS CIVILIZATION MODEL (SPCM): MODEL PERADABAN BERBASIS SPIRITUALITAS UZBEKISTAN UNTUK PENGUATAN KARAKTER DI PENDIDIKAN DASAR - Joni; Moh. Syafi; Andrian Gandi Wijanarko (JISPE Journal of Islamic Primary Education, 2026)
Modern civilization presents a paradox in which technological advancement and material prosperity are accompanied by moral decline, social fragmentation, spiritual disorientation, and ecological degradation. This study aims to analyze the practical spirituality of Uzbek society through the principles of Hosh Dar Dam, Dast ba-kār wa Dil ba-yār, and Hashar, and to develop the Spiritual Pragmatics Civilization Model (SPCM) as a conceptual framework for strengthening character education in primary education. The study employed an interpretive qualitative approach using a comparative ethnopragmatic design conducted in Uzbekistan and Indonesia. Data were collected through participant observation, in-depth interviews, and document analysis, and were analyzed using open coding, ethnopragmatic analysis, comparative civilization analysis, and conceptual model construction. The findings reveal that practical spirituality functions as an internal moral regulatory mechanism through spiritual awareness, work ethics, social solidarity, and ecological responsibility. The principle of Hosh Dar Dam cultivates moral awareness, Dast ba-kār wa Dil ba-yār integrates productivity with spirituality, while Hashar strengthens social cohesion and ecological responsibility. The novelty of this study lies in the development of the Spiritual Pragmatics Civilization Model (SPCM), which systematically integrates these four dimensions into a conceptual framework for strengthening character education. The proposed model contributes theoretically to the advancement of spirituality-based educational studies and offers practical implications for enhancing character education and promoting sustainable development in Indonesia